Genghis Khan and the Mongol empire - Roux, Jean-Paul, 1925- (Discoveries (New York, N.Y.), 2003)
"The legendary Mongol conqueror Genghis Khan (1155-1227) built one of the largest and most powerful empires in all history, striking fear and leaving devastation in his wake. Through their military brilliance, extreme discipline, and innovative weaponry, by 1224 the Mongols had expanded their empire--in which justice ruled, commerce flouished, all religions and races were accepted, and great scientific and artistic strides were made--into modern-day Korea, China, Russia, the Middle East, India, and eastern Europe. This in-depth survey by historian Jean-Paul Roux gives the reader a clear vision of this incomparable leader and the achievements of his mighty empire."--Publisher's description.